2020
DOI: 10.1002/joc.6922
|View full text |Cite
|
Sign up to set email alerts
|

A classification scheme for identifying snowstorms affecting central New York State

Abstract: The Great Lakes region experiences anomalously high seasonal snowfall totals relative to similar latitudes. Although lake‐effect snowstorms are common in this region, snowfall occurs from a variety of storm types. This study examines snowstorms in a subsection of the Lake Ontario basin to develop a classification scheme to categorize the different types of snowstorms affecting the region. From 1985 to 2015, there were 11 different snowstorm types to affect the study area. The classification system was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 87 publications
1
14
1
Order By: Relevance
“…Eichenlaub (1970) suggests that lake-effect storms contribute at least 20% of the seasonal snowfall in areas lee of Lake Superior and Lake Michigan. This estimate is modest, compared to those from other studies that suggest contributions are closer to 50% in other subregions of the Great Lakes basin and during more recent years (Kelly, 1986;Braham and Dungey, 1995;Liu and Moore, 2004;Hartnett, 2020;Pettersen et al, 2020;Suriano and Wortman, 2021).…”
Section: Introductioncontrasting
confidence: 77%
See 3 more Smart Citations
“…Eichenlaub (1970) suggests that lake-effect storms contribute at least 20% of the seasonal snowfall in areas lee of Lake Superior and Lake Michigan. This estimate is modest, compared to those from other studies that suggest contributions are closer to 50% in other subregions of the Great Lakes basin and during more recent years (Kelly, 1986;Braham and Dungey, 1995;Liu and Moore, 2004;Hartnett, 2020;Pettersen et al, 2020;Suriano and Wortman, 2021).…”
Section: Introductioncontrasting
confidence: 77%
“…Seasonal snowfall contributions were determined by identifying every snowstorm to influence central New York State (Figure 1) from the 1995/96 to 2014/15 cold seasons (October to May). Snowstorms were identified using data from the National Weather Service's Cooperative Observer Program (COOP) and are defined as any storm in which at least 0.1 cm of snow was observed for at least two of the two-hundred and two reporting stations within the study area (Perry et al, 2007;Hartnett, 2020; Figure 2). Using the methods outlined by Hartnett (2020), a storm was considered independent from other events if there was at least a 6-h gap in precipitation (e.g., 6-h gap in 15min precipitation records and/or radar) anywhere within the study area.…”
Section: Snowstorm Categorizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Changnon (1968) calculated a 30% increase for the same region and a much higher increase (∼50%) for northwestern Michigan. Hartnett (2020) classified snowstorms affecting central New York into non-direct cyclonic storms and direct cyclonic storms and found that lake effect storms contributed to ∼39.4% of total snowfall for the period of 1985. Hartnett (2020 also suggested that heavy snow storms (>25.4 cm) contributed to more than 50% of total snowfall for every type of snowstorms.…”
Section: Introductionmentioning
confidence: 99%